Effect of Qianghuo Erhuang Decoction on T Regulatory and T Helper 17 Cells in Treatment of Adjuvant-induced Arthritis in Rats. Issue 1 (December 2017) - Qian, Can; Kuang, Mei; Wang, Yong
Abstract QianghuoErhuang Decoction (QED) is an effective recipe in treating rheumatoid arthritis. The present study aimed to explore the effects of QED on Treg and Th17 in adjuvant arthritis (AA) model. The study included 6 group rats: normal control group, AA group, AA + methotrexate (MTX) group, AA + high, moderate, and low dose QED groups. The arthritis score was significantly decreased in the MTX and high-dose QED groups compared with the AA group on days 24 and 28 (P  < 0.01), respectively. The synovial tissue inflammation was attenuated by histological observation, and the proliferation of splenocytes was significantly inhibited in MTX and high-dose QED groups (P  < 0.01). High-dose QED can up-regulated the percentage of Treg cells (P  < 0.01) and down-regulated the percentage of Th17 cells (P  < 0.05). Notably, the serum levels of IL-6, IL-17 and TNF-α were significantly decreased, while TGF-β levels were apparently elevated compared with AA group (P  < 0.05, P  < 0.01). Interestingly, moderate and low-dose QED had no such similar effects. In summary, high-dose QED had a therapeutic effect against adjuvant arthritis and regulated the related cytokine levels in serum. The underlying mechanism might be mediated via restoration of the imbalance in CD4+ T lymphocyte subsets, Treg/Th17.